Bridging the Gap Between Home and School—Perceptions of Classroom Teachers and Principals: Case Studies of Two Jamaican Inner-City Schools. (November 2017) - Kinkead-Clark, Zoyah
Within the past 5 years, the island of Jamaica has aimed to address social issues through the development of a National Parenting Program. Schools too have taken on this task and have sought to bridge the gap between home and school by working with parents in meaningful and sustainable ways. This small-scale study highlights how two inner-city schools have worked to do this. The data for this study were collected over 4 years during visits to the school for the teaching practice in the final year for students in their teacher education bachelor's degree programs. Two research questions were used: (a) How has a partnership program between home and school benefited you and your students? And (b) What are the strategies that can be employed by the school to facilitate a smooth, successful reciprocal relationship? From the data collected, three dominant themes emerged from the findings: (a) home–school relations matter, (b) parent empowerment and teacher validation, and (c) understanding diverse cultures.